Community conserved areas in Sabah, Malaysia: sustainability and impacts on livelihoods - Loke, Vivienne Pei Wen (2024)
Community conserved areas (CCAs) have tremendous potential for supporting biodiversity conservation, providing ecosystem services, conserving local ecological knowledge and providing better livelihood outcomes for communities. This study was conducted in two CCAs around the Kinabalu Ecolinc zone, Sabah, Malaysia to: i) understand the factors contributing to the sustainability of CCAs, and ii) assess the impacts of CCAs on the livelihoods of indigenous communities. In each CCA, 80 household interviews and one focus group discussion were conducted. Household interviews collected information on their livelihood capitals, participation in Kinabalu Ecolinc activities, satisfaction with Ecolinc’s activities, and perception on Ecolinc’s management, benefits and sustainability. Information on their CCA management strategies, livelihood and tourism development activities, and the sustainability of the CCAs based on Ostrom’s Design Principle (ODP) were collected through focus group discussions. Both CCAs are found to be sustainably managed by their respective communities, conforming to all eight ODPs. Principles such as conflict resolutions (ODP 6), gaining formal recognition (ODP 7) and having nested enterprises (ODP 8) could be further enhanced to strengthen the land tenure security for the long-term sustainable management of the CCAs. Participation of the communities in CCA projects’ management affects the sustainability of the project. CCAs and Ecolinc’s activities have a positive contribution to the livelihoods of indigenous communities. Continuous institutional support from government and private sectors would be essential for community development projects, especially in communities that face more shortages in food security. This study proves that indigenous communities are capable of managing their natural resources sustainably and provides insights on the factors that could enhance the sustainable management of CCAs.